Pengaruh Mental Accounting dan Norma Subjektif terhadap Consumptive Behavior Gen Z dalam Menggunakan E-paylater (Studi Kasus pada Mahasiswa Jurusan Akuntansi di Bangka Belitung) - Aprilian, Rahil Imainul; Anggita, Wenni (Jurnal EMT KITA, 2025)
Technological advancements have significantly transformed Generation Z’s consumption behavior, particularly in the use of digital financial services such as e-paylater. This study aims to analyze the influence of mental accounting and subjective norms on consumptive behavior using the Theory of Planned Behavior (TPB) approach. A quantitative method was applied to 146 accounting students in Bangka Belitung who had completed courses in portfolio theory and investment and actively used digital platforms. The results show that both mental accounting (p = 0.038) and subjective norms (p = 0.01) significantly affect consumptive behavior, with subjective norms being the dominant factor. Social pressure from peers and the way individuals mentally categorize money were found to influence consumption decisions. These findings support the TPB framework, where social norms and internal cognitive processes contribute to behavioral intention and actual behavior. The study highlights the need to enhance digital financial literacy and strengthen self-control to reduce the negative effects of social pressure and cognitive biases in financial decision-making. Digital platforms are also encouraged to provide budgeting tools and financial education features to support more mindful consumption behavior.